Geographical subdivision of Alviniconcha snail populations in the Indian Ocean hydrothermal vent regions - Jang, Sook-Jin; Cho, Soo-Yeon; Li, Chuyu; Zhou, Yadong; Wang, Hui; Sun, Jin; Patra, Ajit Kumar; Won, Yong-Jin (Frontiers in Marine Science, 2023)
The hairy snails of the genus Alviniconcha are representative deep-sea hydrothermal vent animals distributed across the Western Pacific and Indian Ocean. Out of six known species in the genus Alviniconcha, only one nominal species of A. marisindica was found in the Indian Ocean from the Carlsberg Ridge (CR), Central Indian Ridge (CIR) to the northern part of Southwest Indian Ridge (SWIR) and Southeast Indian Ridge (SEIR). Recently, the Alviniconcha snails were found at three new vent fields, named Onnare, Onbada, and Onnuri, in the northern CIR, which promotes a more comprehensive phylogeographic study of this species. Here, we examined the phylogeography and connectivity of the Alviniconcha snails among seven vent fields representing the CR and CIR based on DNA sequence data of a mitochondrial COI gene and two protein-coding nuclear genes. Phylogenetic inferences revealed that the Alviniconcha snails of the newly found in the northern CIR and two vent fields of Wocan and Tianxiu in the CR were divergent with the previously identified A. marisindica in the southern CIR and mitochondrial COI data supported the divergence with at least greater than 3% sequence divergence. Population structure analyses based on the three genetic markers detected a phylogeographic boundary between Onnuri and Solitaire that divides the whole snail populations into northern and southern groups with a low migration rate. The high degree of genetic disconnection around the ‘Onnuri’ boundary suggests that the Alviniconcha snails in the Indian Ocean may undergo allopatric speciation. The border may similarly act as a dispersal barrier to many other vent species co-distributed in the CIR. This study would expand understanding the speciation and connectivity of vent species in the Indian Ocean.